Analysis the effect of handling facilities on the quality of fishes landed at fish auction market - Ratih Purnama Sari; Yaser Krisnafi; Ayu Rizky Amalia; Edy Miswar (Depik, 2024)
Research related to the influence of facilities on the quality of fish landed and auctioned has been done previously, but the catches under this study are still limited to large pelagic fish with complex fish auction facilities. This study was conducted for small pelagic fish where the handling facilities at this location are still very limited. Therefore, survey research with purpose to analyze the effect of handling facilities (ships, fish auction sites, baskets) on the quality of small pelagic fish. The data taken is daily data with the method of observation at the location on the ship, fish auction place, and baskets. The species that taken were Eleutheronema tetradactylum, Ilisha elongate, Pampus argenteus, and Johnius trachychepalus. Each species consists of 5 individuals. Its tests was done by looking at the organoleptic and pH values. The tests were done to every species of fish. The pH value was obtained by testing the fish meat sample on the meat pH meter, while the organoleptic value was obtained by looking at the physical condition of the fish using a score sheet of fresh fish quality parameters. Then after the results are obtained, an analysis is carried out to determine the magnitude of facility influence on fish quality by simple linear regression analysis. The organoleptic values of four kinds of samples were on average 6.84 - 4.95, while the pH values measured in these fish ranged from 6.3 - 5.94. The effect of fish handling facilities on the organoleptic value is 82% compared to other factors. The fish quality as measured by the organoleptic test showed a fairly good quality, while measured by the pH test showed good results. Handling facilities do not greatly affect the quality of fish and there are other factors that can affect the decline in fish quality other than facilities. The relationship between fish handling facilities and quality can give an overview of the contribution of handling facilities to fish quality.Keywords:Fish auction marketFish qualityHandling facilities